From quarks and gluons to quantum gravity : (World Scientific, 2002)
The purpose of the School was to focus attention on the theoretical and phenomenological developments in gauge theories, as well as in all the other sectors of subnuclear physics. Experimental highights from the most relevant sources of new data were presented and discussed, including the latest news on theoretical developments in quantizing the gravitational forces.